A case of suspected propofol infusion syndrome after abdominal aortic aneurysm surgery - Atsushi Guntani; Ryosuke Yoshiga; Shinsuke Mii (Surgical Case Reports, 2020)
Abstract Background Propofol infusion syndrome (PRIS) is a rare but potentially lethal side effect during propofol administration. Case presentation The patient was scheduled for abdominal aortic aneurysm resection and reconstruction. Propofol used during sedation for ventilation after the surgery-induced rhabdomyolysis, heart failure, and renal failure. Discontinuation of propofol administration led to a dramatic improvement in the fatal symptoms, resulting in a diagnosis of PRIS. Conclusions We herein report a rare case of a PRIS during sedation in the intensive care unit after abdominal aortic aneurysm surgery. Physicians using propofol should therefore be aware of the potential risk of PRIS.